Epigenetic regulation of high glucose-induced proinflammatory cytokine productionin monocytes by curcumin - Yun, Jung-Mi (2010)
Diabetes is a pro-inflammatory state. We have previously shown increased monocyte pro-inflammatory cytokines in patients with Type 1 and Type 2 diabetes. High glucose induces pro-inflammatory cytokines via epigenetic changes. Curcumin, a polyphenol responsible for the yellow color of the spice turmeric, is known to exert potent anti-inflammatory activity in vitro. Recent studies indicate that it may regulate chromatin remodeling by inhibiting histone acetylation. In this study, we aimed to test the effect of curcumin on histone acetylation and pro-inflammatory cytokine secretion under high-glucose conditions in human monocytes. Human monocytic (THP-1) cells were cultured in presence of mannitol (osmolar control, mannitol) or normoglycemic (NG, 5.5 mmol/L glucose) or hyperglycemic (HG, 25 mmol/L glucose) conditions in absence or presence of curcumin (1.5-12.5μM) for 72 h. Cytokine level, nuclear factor κB (NF-κB) transactivation, histone deacetylases (HDACs) activity, histone acetylases (HATs) activity were measured by western blots, qRT-PCR, ELISA, Immunofluorescence (IF) staining. HG significantly induced histone acetylation, NF-κB activity and pro-inflammatory cytokine (IL-6, TNF-α and MCP-1) release from THP-1 cells. Curcumin suppressed NF-κB binding and cytokine release in THP-1 cells. Also, since p300 histone acetyltransferase is a coactivator of NF-κB, we examined its acetylation. Curcumin treatment also significantly reduced HAT activity, level of p300 and acetylated CBP/p300 gene expression, and induced histone deacetylase 2 (HDAC2) expression by curcumin. These results indicate that curcumin decreases HG-induced cytokine production in monocytes via epigenetic changes involving NF-κB. In conclusion, curcumin supplementation by reducing vascular inflammation may prevent diabetic complications.